Upregulation of FOXM1 induces genomic instability in human epidermal keratinocytes - Philpott Michael P (Molecular Cancer, 2010)
Abstract Background The human cell cycle transcription factor FOXM1 is known to play a key role in regulating timely mitotic progression and accurate chromosomal segregation during cell division. Deregulation of FOXM1 has been linked to a majority of human cancers. We previously showed that FOXM1 was upregulated in basal cell carcinoma and recently reported that upregulation of FOXM1 precedes malignancy in a number of solid human cancer types including oral, oesophagus, lung, breast, kidney, bladder and uterus. This indicates that upregulation of FOXM1 may be an early molecular signal required for aberrant cell cycle and cancer initiation. Results The present study investigated the putative early mechanism of UVB and FOXM1 in skin cancer initiation. We have demonstrated that UVB dose-dependently increased FOXM1 protein levels through protein stabilisation and accumulation rather than de novo mRNA expression in human epidermal keratinocytes. FOXM1 upregulation in primary human keratinocytes triggered pro-apoptotic/DNA-damage checkpoint response genes such as p21, p38 MAPK, p53 and PARP, however, without causing significant cell cycle arrest or cell death. Using a high-resolution Affymetrix genome-wide single nucleotide polymorphism (SNP) mapping technique, we provided the evidence that FOXM1 upregulation in epidermal keratinocytes is sufficient to induce genomic instability, in the form of loss of heterozygosity (LOH) and copy number variations (CNV). FOXM1-induced genomic instability was significantly enhanced and accumulated with increasing cell passage and this instability was increased even further upon exposure to UVB resulting in whole chromosomal gain (7p21.3-7q36.3) and segmental LOH (6q25.1-6q25.3). Conclusion We hypothesise that prolonged and repeated UVB exposure selects for skin cells bearing stable FOXM1 protein causes aberrant cell cycle checkpoint thereby allowing ectopic cell cycle entry and subsequent genomic instability. The aberrant upregulation of FOXM1 serves as a 'first hit' where cells acquire genomic instability which in turn predisposes cells to a 'second hit' whereby DNA-damage checkpoint response (eg. p53 or p16) is abolished to allow damaged cells to proliferate and accumulate genetic aberrations/mutations required for cancer initiation.